Community involvement, trust, and health-related outcomes among older adults in India: a population-based, multilevel, cross-sectional study. (17th October 2018) - Joe, William; Perkins, Jessica M; Subramanian, S V
Abstract: Objectives: this study examined whether individual and contextual measures of structural and cognitive social capital were associated with six health-related outcomes across older adults in India. Methods: data were collected from a representative sample of adults aged 60 and above across India in 2011–12 ( n = 9, 174). Personal community involvement and having someone to trust represented individual measures of structural and cognitive social capital. These measures were then aggregated to represent contextual measures of social capital, that is, the mean village level of community involvement and the village proportion having someone to trust. To examine associations between all four social capital indicators and six outcomes including self-rated health, psychological well-being, subjective well-being, memory, activities of daily living (ADL), and instrumental activities of daily living, we fit pooled, sex-stratified, and place-stratified multilevel regression models and adjusted for demographic and socio-economic factors. Results: personal community involvement was positively associated with all outcomes among the full sample. Adjusted odds ratios ranged from 1.05 (95% CI 1.02; 1.08) for good self-rated health to 1.42 (95% CI 1.33; 1.53) for high-ADL function. Personally having someone to trust was associated with four outcomes. Village-level social capital measures were less frequently associated with outcomes than personal social capital measures. Association strength between six health-related outcomes and individual and contextual measures of structural and cognitive social capital varied, however, among older people in India by sex, place and outcome. Discussion: interventions to promote healthy ageing by increasing community involvement and trust may need to be tailored to population subgroups.